The Cultural Aspect of Translation - Iman Hamza Othman; Alan Hoshyar Azaldin; Rfaai Rashid Mohammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Translation is an interdisciplinary practice with texts of different types and properties. However, the role that translation has played through the course of time has enabled cultures and societies to communicate and convey knowledge but still the Arabic text is mis-translated in the European societies. Due to its importance ideologically and conceptually, it is important for the translator to acquaint him\herself with appropriate information regarding culture and how it is realized in translation. The following paper tries to approach the issue of culture in translation by trying to define it and then tackles different approaches regarding culture and the translation theory. It then moves to present some views on the cultural component when translating. Through these discussions and opinions, the researchers of this paper hope to make readers gain a better understanding of culture and its importance when translating.